1979
DOI: 10.1002/mpo.2950070415
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity in the treatment of acute lymphoblastic leukaemia

Abstract: Serial liver function tests and percutaneous liver biopsies were performed on 21 children receiving treatment for acute lymphoblastic leukaemia (ALL). The patients received continuing chemotherapy either with daily 6-mercaptopurine and weekly methotrexate or with five-day pulses of these drugs every three weeks. Liver function tests were transiently abnormal in the majority of children, but the abnormalities bore no relationship to the histology of the liver biopsy. Mild inflammatory and fatty changes were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
0
16
2
Order By: Relevance
“…This may be related to the means of detection used; although light microscopic changes were minimal, electron microscopic examination of liver biopsy specimens from children given MTX and 6-MP showed significant abnormalities in all patients [166]. In another study, liver biopsy specimens from children receiving maintenance therapy with 6-MP and MTX revealed mild inflammatory and fatty changes in many, and early portal fibrosis in 3 of 16 biopsies after more than two years of therapy [167]. Interpretation of reported cases has been complicated by the fact that children who present at an older age and require more transfusions are more likely to develop increased ALT values in a pattern consistent with non-A, non-B hepatitis [168].…”
Section: Combination Chemotherapymentioning
confidence: 99%
“…This may be related to the means of detection used; although light microscopic changes were minimal, electron microscopic examination of liver biopsy specimens from children given MTX and 6-MP showed significant abnormalities in all patients [166]. In another study, liver biopsy specimens from children receiving maintenance therapy with 6-MP and MTX revealed mild inflammatory and fatty changes in many, and early portal fibrosis in 3 of 16 biopsies after more than two years of therapy [167]. Interpretation of reported cases has been complicated by the fact that children who present at an older age and require more transfusions are more likely to develop increased ALT values in a pattern consistent with non-A, non-B hepatitis [168].…”
Section: Combination Chemotherapymentioning
confidence: 99%
“…Both drugs are well known to be hepatotoxic [ 1-41, and fibrosis of varying degree after prolonged use of these agents has been demonstrated on liver biopsy ; even cirrhotic changes [3,8] and the development of hepatoma [9] have been reported. However, routine liver function tests normalize promptly after the cessation of therapy in the majority of patients [l], and biopsy findings and liver function tests were not necessarily found to be correlated [5,6]. Since it is important to know the effects of these liver abnormalities on liver status after the cessation of therapy, we investigated liver function status in patients treated for ALL during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas a number of these studies have set focus on the relation between pathological liver function tests and the presence of an abnormal liver histology (Nesbit et al, 1976;McIntosh et al, 1977;Topley et al, 1979), the main purpose of the present study was to explore the relation between relapse risk and the rise in serum AT, the most commonly applied test to detect liver dysfunction used by the departments participating in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The rises in liver enzymes during MT are in most cases mild and transient with normalisation within a few months following the cessation of therapy. For patients with severe liver dysfunction with affected prothrombin time, jaundice or very high levels of liver enzymes, a liver biopsy may offer a guide to whether dose modifications should take place, though often no correlation exists between pathological liver function tests and histology (Topley et al, 1979). Parker et al (1980) suggested that analysing plasma concentration profiles of drugs could be helpful in determining dose modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation